Fungi associated with termites and their nests in eucalyptus plantations - GUTIÉRREZ, ANA ISABEL; SALDARRIAGA-O., YAMILLÉ; URJBE-S., SANDRA; PINEDA-G., FABIO (Revista Colombiana de Entomología, 2004)
The region of San Sebastián of Buenavista, Magdalena (Colombia), is characterized for being one of the most important producers of lumber derived from eucalyptus plantations. At present. large economic losses have been registered for lumber companies operating in San Sebastián due to the damage caused by termites. These losses reach approximately 83,6% of the production in the study. The control measures carried out are few, mainly using chemical insecticides. In this region, studies have not been conducted on recognizing the termites that attack eucalyptus nor on the microorganisms associated with them. These studies are important because sorne microorganisms may be regulating termite populatlons under natural conditions, or have potential as microbiological control agents. In this paper we report the genera of termites present in eucalyptus and the fungi associated with their nests and nearby substrates. The termites found belong to the genera Microcerotermes, Amitermes and Coptotermes. A total of 252 fungal isolates corresponding to 31 genera and 29 species were obtained. The fungal isolates were grouped into categories according to their origin. We identify those isolates recognized as entomopathogenics or previously reported in association with termites. Among the most important fungí were Aspergillus spp. (33,3%), FUsarium spp. (21 %), Penicillium spp. (7,9%), Trichoderma spp. (6,8%), Paecilomyces spp. (4,8%) and t:ntomophthora spp. (2,4%).